Healthcare Engagement and Encounters in a Rural State: A Focus Group Study - Reshmi Singh; Heather Scott; Kem Krueger; Erin J Bush (University of Minnesota Libraries Publishing, 2018)
Introduction: Rural populations have many barriers to quality health care including lack of access to primary care and specialty care and a greater likelihood to be underinsured or uninsured. They are also less likely to use preventive screening, or to participate in self-care and engage in their health when compared to urban residents. The purpose of this paper was to describe patients' healthcare experiences in a rural western state focusing on their healthcare expectations and engagement. Methods: This qualitative study was conducted using a focus group protocol to elicit rural patients' healthcare experiences. A purposeful sample of English speaking adult residents from a single county who were willing to discuss their healthcare experiences was included. Patients and community members (21 years and older) were recruited through a local hospital as well as via flyers posted throughout the community. Each audio-recorded group took about two hours. A total of 15 focus groups were conducted to obtain sufficient text for theoretical saturation and thematic analysis. Each group had a range of 3-8 participants. A $25 visa gift card and lunch were provided for each participant as an incentive. Results: 'Encounters with Healthcare Professionals' and 'Engagement in Health' were the two dominant dimensions with two themes each. Themes centered around what characterized the best or worst encounters. Trust and Communication - both were based on time spent with the provider and establishment of rapport with the providers. The best encounters were those with health care providers or pharmacists who had sufficient time, adequately explained a diagnosis and new medications did not dismiss patient concerns, and treated individuals with respect. Typical responses describing the worst encounters included examples of misdiagnosis, dismissing patient's symptoms, healthcare professionals whose attention was not focused on the patient, pushing too many medications, rushed encounters, and providers with poor bedside manner. 'Engagement in Health' dimension included the theme of Self-management Process such as taking things one day at a time, taking medication daily, and good stress management. The second theme was Barriers to Engagement and included issues regarding inclement weather, lack of sidewalks, stress, lack of time and the financial constraints for eating healthy, going to a gym, and/or problems with payer source. Participants also described a number of technological tools they utilized to engage with their healthcare including appointment reminders, health-based websites, symptom trackers, online portal systems for health care records, and online bill pay. Many used apps on smart phones to track calories and exercise as well as online community groups to encourage fitness. Conclusions: The results from this study highlighted some of the gaps in healthcare for rural areas. A large number of participants indicated a lack of trust of their providers and only a few had any communicative interaction with their pharmacist. Future studies could evaluate training designed to teach healthcare providers and pharmacists how to engage patients in their own care. Use of technology by healthcare providers might be another way to improve healthcare engagement. Conflict of Interest "We declare no conflicts of interest or financial interests that the authors or members of their immediate families have in any product or service discussed in the manuscript, including grants (pending or received), employment, gifts, stock holdings or options, honoraria, consultancies, expert testimony, patents and royalties". Acknowledgements: This study was funded by the University of Wyoming College of Health Sciences (UW CHS) Faculty Seed Grant awarded to first author Dr. Singh in April 2015. Interim results of this study have been presented at the Health Literacy Research Conference (HARC) in November 2015. Treatment of Human Subjects: IRB review/approval required and obtained   Type: Original Research